Manifestations of symmetry and asymmetry of the peak torque produced by the muscles responsible for rotational movements among judo competitors, representatives of the National Teams of Poland and Belgium - Walowski, K.; Poliszczuk, T.; Poliszczuk, D. (Journal of Combat Sports and Martial Arts, 2016)
Introduction. The problem of rotational movements generated by the human body when practicing various sport disciplines is becoming increasingly popular among researchers. However, the knowledge of peak torque symmetry in muscles responsible for these movements in the trunk area is still insufficient. Based on the measurement results, an attempt was made to compare peak torque values in muscles responsible for rotational movements of the trunk in the sample of Polish National Team representatives from Poland and Belgium. Material and methods. The study group comprised the male judo competitors of Polish (n=16) and Belgian National Teams (n=12), participating in the meeting at the Olympic Training Center in Zakopane, Poland. The values of peak torque generated during rotational movements of the trunk under static conditions were measured. For this purpose, a special device was constructed. Statistical analysis was conducted using ANOVA test and t-test. Results. The peak torque values generated by the muscles responsible for trunk rotation did not significantly differ between groups. Significantly greater opportunities of generating peak torque were shown for selected angular positions. In both groups a slight asymmetry was found in the muscles responsible for trunk rotation. Conclusions. The analysis of specialist literature and results of the conducted study indicate that high levels of training in judo competitors correspond to slight differences in muscle strength of the muscles responsible for trunk rotation. Training directed at symmetrization of peak torque in muscles may compensate congenital asymmetry and should be conducted at every stage of training.